2002
DOI: 10.1093/emboj/21.8.1930
|View full text |Cite
|
Sign up to set email alerts
|

A photosystem II-associated carbonic anhydrase regulates the efficiency of photosynthetic oxygen evolution

Abstract: We show for the first time that Cah3, a carbonic anhydrase associated with the photosystem II (PSII) donor side in Chlamydomonas reinhardtii, regulates the water oxidation reaction. The mutant cia3, lacking Cah3 activity, has an impaired water splitting capacity, as shown for intact cells, thylakoids and PSII particles. To compensate this impairment, the mutant overproduces PSII reaction centres (1.6 times more than wild type). We present compelling evidence that the mutant has an average of two manganese atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
86
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 33 publications
8
86
2
2
Order By: Relevance
“…This would have a physiological meaning, ensuring the prompt removal of protons released during water oxidation. The latter process can be a part of the system preventing photoinhibition, as was proposed previously [8].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This would have a physiological meaning, ensuring the prompt removal of protons released during water oxidation. The latter process can be a part of the system preventing photoinhibition, as was proposed previously [8].…”
Section: Discussionmentioning
confidence: 59%
“…Previously, we revealed that the pea thylakoid membrane fragments enriched with PSII demonstrated a noticeable dehydrase CA activity only after the treatments either with detergent or salt, while this activity was high in the core complex of PSII [6,7]. The presence of CA activity was also found in PSII core complexes from Chlamydomonas reinhardtii [8]. Using the affinity electrophoresis and affinity chromatography of n-dodecyl-b-maltoside (DM) extract of PSII membrane isolated from wheat, we got in the present work new convincing data, which permitted to locate PSII CA activity in the core complex.…”
Section: Introductionmentioning
confidence: 88%
“…As Cah-3 is known to be associated with polypeptides of photosystem (PS) II of C. reinhardtii thylakoid membranes (Park et al, 1999;Villarejo et al, 2002), it was necessary to be sure that the signal observed in the cell envelope fraction of M. chthonoplastes did not result from cross-contamination of this fraction with thylakoid membranes from the cyanobacterium. Antibodies against D1 (PsbA), a major protein of PS II, was used as a specific marker for thylakoid membranes (Nishiyama et al, 2001).…”
Section: Identification Of M Chthonoplastes Extracellular A-camentioning
confidence: 99%
“…In the present study using higher plant PSII membranes, we specifically evaluate a recently suggested role of weakly bound HCO − 3 , namely, that it acts as an acceptor for, and transporter of, protons produced by water splitting in the OEC (20)(21)(22).…”
mentioning
confidence: 99%